(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2025)
Adolescence is a critical period characterized by significant biological changes and extensive exposure to ideal body standards on social media, which can influence body image and nutritional status. This study aims to analyze the correlation between social media usage intensity, body image, diet quality, physical activity, and nutritional status among adolescents at SMAN 1 Bogor. A cross-sectional design was employed with 87 students selected through purposive sampling. Data were collected through direct measurements, structured interviews, and questionnaires. Body image perception data were measured using the Body Shape Questionnaire (BSQ), social media use intensity was measured using the Social Media Use Intensity Scale (SIPMS), diet quality was measured using the Diet Quality Index for Adolescents (DQI-A), and physical activity was measured using the International Physical Activity Questionnaire Short Form (IPAQ-SF). Meanwhile, nutritional status data were obtained through direct anthropometric measurements. The results showed that 53% of subjects were categorized as heavy social media users, 60% had a positive body image, 41% engaged in moderate physical activity, and 70% had good nutritional status. The average Diet Quality Index for Adolescents (DQI-A) score was 40.7%, indicating poor diet quality. Statistical analysis revealed a significant correlation between social media usage intensity and body image (p<0.05), as well as between body image and nutritional status (p<0.05). However, no significant correlation was found between body image and diet quality or physical activity, nor between physical activity and diet quality with nutritional status (p>0.05). These findings highlight the need for more comprehensive interventions to promote healthy behaviors and positive self-perception among adolescents.